2024
DOI: 10.1186/s12877-024-04742-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, country-specific prescribing patterns and determinants of benzodiazepine use in community-residing older adults in 7 European countries

Anna Lukačišinová,
Jindra Reissigová,
Maja Ortner-Hadžiabdić
et al.

Abstract: Background The use of benzodiazepines (BZDs) in older population is often accompanied by drug-related complications. Inappropriate BZD use significantly alters older adults’ clinical and functional status. This study compares the prevalence, prescribing patterns and factors associated with BZD use in community-dwelling older patients in 7 European countries. Methods International, cross-sectional study was conducted in community-dwelling older adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…According to the Annual Report on Drug Use in Croatia in 2022, diazepam and alprazolam were among the top 10 medications most often used in this country [ 46 ]. The EuroAgeism project reported similar patterns to those that we observed among NH older persons, with diazepam being the most prescribed benzodiazepine in Croatia also among community-dwelling older adults [ 43 ]. A national study using claims data confirmed that benzodiazepine prescriptions increased by 4.1% in Croatia between 2015 and 2016 [ 39 ]; therefore, strategies to improve the appropriateness of benzodiazepine prescribing in Croatia appear to be needed.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…According to the Annual Report on Drug Use in Croatia in 2022, diazepam and alprazolam were among the top 10 medications most often used in this country [ 46 ]. The EuroAgeism project reported similar patterns to those that we observed among NH older persons, with diazepam being the most prescribed benzodiazepine in Croatia also among community-dwelling older adults [ 43 ]. A national study using claims data confirmed that benzodiazepine prescriptions increased by 4.1% in Croatia between 2015 and 2016 [ 39 ]; therefore, strategies to improve the appropriateness of benzodiazepine prescribing in Croatia appear to be needed.…”
Section: Discussionsupporting
confidence: 69%
“…Another contributing factor that could explain the high prevalence of potentially inappropriate benzodiazepine prescribing and regional variations is the absence of national guidelines on rational benzodiazepine prescribing in geriatric patients in Croatia [ 39 ]. In the EuroAgeism H2020 project (2017–2022) conducted in older patients visiting pharmacies in eight European countries, the exposure to benzodiazepines in Croatia was the highest (35.5%) across all included countries (with the lowest prevalence in Turkey, 0.7%) [ 43 ]. The EuroAgeism project [ 44 ] aimed to identify the most common prescribing problems in older adults in Central and South-Eastern Europe (in the Czech Republic, Estonia, Serbia, Croatia, Bulgaria, Turkey and Spain) to support the need for availability of clinical pharmacy services.…”
Section: Discussionmentioning
confidence: 99%